Deskripsi Kesulitan Siswa dalam Menyelesaikan Soal Matematika Materi Dimensi Tiga pada Kelas VIII - Nurrahmah; Djadir; Ilham (Program of Mathematics Education Department of Mathematics Faculty of Mathematics and Natural Sciences (FMIPA) Universitas Negeri Makassar (UNM), 2018)
This research is a qualitative research, it amis to describe the students’ difficulties in solving three-dimensional problems on the flat-side material. By using purposive sampling technique, then the subjects in this research were 3 students on grade VIII, that is subject KF, subject KK, subject KO and subject KP. For data collection, the instruments used are diagnostic test and interviews. The results showed that (1) Subject KF having facts difficulty relating to the inability to interpret the final results obtained; identify examples and non-example of the concept and an inability to assert concepts, inability to further identify the subject seen from an inability to answer correctly questions provided. The inability of the subject confirms looks of doubt in giving the reasons selecting and deselecting the image. Subject KK also have difficulty in distinguishing geometrical geometrical prism and pyramid; (3) Subject KO having operating difficulty. This is evident from the subject mistake in conducting the operation. Subject KO wrong in doing operations related to the sequence of operations and how to solve equations using division; and (4) Subject KP having principle difficulty. This is evident from the inability of the subject determines the appropriate formula with the given problem. Subject KP capable of memorizing formulas but can not adjust the formula to the problem.